Differences in Adipose Gene Expression Profiles between Male and Female Even Reindeer (Rangifer tarandus) in Sakha (Yakutia) - Weldenegodguad, Melak; Kantanen, Juha; Peippo, Jaana; Pokharel, Kisun (MDPI AG, 2022)
Reindeer are native to harsh northern Eurasian environments which are characterized by long and cold winters, short summers, and limited pasture vegetation. Adipose tissues play a significant role in these animals by modulating energy metabolism, immunity, and reproduction. Here, we have investigated the transcriptome profiles of metacarpal, perirenal, and prescapular adipose tissues in Even reindeer and searched for genes that were differentially expressed in male and female individuals. A total of 15,551 genes were expressed, where the transcriptome profile of metacarpal adipose tissue was found to be distinct from that of perirenal and prescapular adipose tissues. Interestingly, 10 genes, including PRDM9, which is known to have an important role in adaptation and speciation in reindeer, were always upregulated in all three tissues of male reindeer.
Keywords: reindeer; adipose tissues; gene expression; male animals; female animals; adaptation; poro; rasvakudokset; geeniekspressio; uros; naaras; fat tissue; gender; mRNA